STRUKTUR, ISI, DAN UNSUR KEBAHASAAN TEKS PROSEDUR KARYA SISWA KELAS XI MIPA SMA NEGERI 5 PADANG - Anesha Al-vidril (Universitas Negeri Padang, 2021)
This study aims to describe the structure, content, and linguistic elements ofprocedural texts for class XI MIPA students at SMA Negeri 5 Padang. This research is aqualitative research using descriptive method. The data of this study, namely thestructure, content and linguistic elements of procedure texts were obtained from 30procedural texts written by class XI MIPA students at SMA Negeri 5 Padang. Theresearch instrument is the researcher himself. Data analysis is done by describing thedata, analyzing the data, and discussing the data based on theory. Based on the resultsof the study, it was concluded that in terms of the structure of the procedural text,students of class XI MIPA SMA Negeri 5 Padang tended to use two parts of thestructure, namely the steps and the closing. In terms of the content of the proceduraltext, the students of class XI MIPA SMA Negeri 5 Padang were able to write down thecontents of the procedure text correctly. This is evident from all the procedure textsthat have been analyzed, most of the students have written procedure textssystematically and in detail, containing steps, and there are sequence numbers. Interms of linguistic elements, students of class XI MIPA SMA Negeri 5 Padang have beenable to use the linguistic elements of procedural texts appropriately.